2016
DOI: 10.1016/j.bbadis.2016.08.005
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of calpain reduces lipotoxicity-induced cardiac injury by preventing endoplasmic reticulum stress

Abstract: Diabetes and obesity are prevalent in westernized countries. In both conditions, excessive fatty acid uptake by cardiomyocytes induces cardiac lipotoxicity, an important mechanism contributing to diabetic cardiomyopathy. This study investigated the effect of calpain disruption on cardiac lipotoxicity. Cardiac-specific capns1 knockout mice and their wild-type littermates (male, age of 4 weeks) were fed a high fat diet (HFD) or normal diet for 20 weeks. HFD increased body weight, altered blood lipid profiles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Although skeletal muscle atrophy probably not regulated by a single mechanism, but a complex one, the calcium-dependent cysteine proteases, calpain also considered as one of the main culprit of protein degradation [ 36 ]. A growing evidence depicted that both calpain and the ubiquitin-proteasome system act synergistically and in a coordinated manner during sepsis induced muscle proteolysis [ 37 ]. The present study findings also described a significant increase in calpain activity on 14d CHH exposure, which was accompanied by an increase in intracellular [Ca 2+ ] (~3 fold), which is rate limiting co-factor of calpain.…”
Section: Discussionmentioning
confidence: 99%
“…Although skeletal muscle atrophy probably not regulated by a single mechanism, but a complex one, the calcium-dependent cysteine proteases, calpain also considered as one of the main culprit of protein degradation [ 36 ]. A growing evidence depicted that both calpain and the ubiquitin-proteasome system act synergistically and in a coordinated manner during sepsis induced muscle proteolysis [ 37 ]. The present study findings also described a significant increase in calpain activity on 14d CHH exposure, which was accompanied by an increase in intracellular [Ca 2+ ] (~3 fold), which is rate limiting co-factor of calpain.…”
Section: Discussionmentioning
confidence: 99%
“…During heart failure, ER stress in cardiomyocytes causes specific morphological changes, suggesting its involvement in cardiac pathophysiologic processes (4)(5)(6). These changes in ER morphology were concomitant with modifications of molecules, such as tumor necrosis factor-α (TNF-α), caspase 3, p53 upregulated modulator of apoptosis (PUMA), and glucose regulated protein 94 (GRP 94), that regulate ER stress-related pathological processes including hypoxia, production of reactive oxygen species (ROS), enhanced protein synthesis, and induction of lipotoxicity (6,7). ER stress has also been detected in both hypertrophic and failure phases induced by transverse aortic constriction in an animal model (5), and is potentially associated with the pathogenesis of human heart failure, as evidenced by the increased expression of binding immunoglobulin protein (BIP, also referred to as GRP78), an ER chaperone and signaling regulator (8), in failing human hearts (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic overexpression of the endogenous calpain inhibitor, calpastatin, protects against myocardial dysfunction in models such as myocardial infarction (26) and endotoxemia (27) . The Peng group has also used genetic deletion of calpain-4, a regulatory subunit for both calpain-1 and calpain-2, to demonstrate the protective effect of inhibiting calpain activity on cardiac function, deleterious reactive oxygen species production, endoplasmic reticulum stress, and mitochondrial metabolic function in multiple different experimental models, including diabetes, ischemia (8) , high-fat diet (28) , and endotoxemia (29) . Studies have also explored the use of MDL-28170 in the acute heart failure model of cardiac ischemia/reperfusion injury and found that administration of the calpain inhibition at the time of injury limits ischemia/reperfusion-induced infarction (30) .…”
Section: Discussionmentioning
confidence: 99%